Coming home: The return of migrant workers with illness or work-related injuries in China's Hubei and Sichuan provinces - Chuanbo Chen; Shijun Ding; Sarah Cook; Myra Pong (United Nations Research Institute for Social Development (UNRISD), 2014)
There is increasing recognition that rural-urban migration has complex health effects. internationally, the migrants state of health has been investigated intensively, and the health status of those migrants who return to their hometowns or rural villages is now receiving greater attention. These studies have led to debates surrounding what has become known as the "healthy migrant phenomenon" by which the countryside exports good health while importing ill health. In China, the number of internal migrant workers has increased rapidly, from an estimated 100 million in 2002 to 160 million in 2011, and their health status is now receiving increasing attention from both the government and scholars. In particular, more attention is being paid to issues concerning the transmission of infectious diseases, maternal health, and occupational disease and injuries. The "healthy migrant phenomenon" has also been observed in the Chinese context. However, the health effects of migration in China (as elsewhere) are extremely complex, both in terms of the physical impact on individuals and the socioeconomic consequences for individuals, households and communities in both sending and receiving areas. There are two main ways in which rural-urban migration and its health implications can be viewed. First, younger and healthier people are more likely to migrate to cities to seek jobs, while the elderly, weak or sick are more likely to remain in their rural home villages. Second, migrants who have a major illness or injury and/or need care are likely to return to their home villages to seek support from their families or communities. Migrant workers who suffer from illness/injuries and subsequently choose to return to their home villages in rural areas often disappear from the public eye and receive little attention. Nonetheless, the burden of taking care of these migrants has important policy and practical implications, not only for the distribution of health care resources, but also for the economic and care burden on the families of these migrants. The central focus of this paper is on the population of return migrants with illness/injuries in China. It starts by providing an overview of the analytical framework used, followed by a discussion of data collection and methods. The rest of the paper then investigates the changing pattern of return migration in China (that is, how the countryside is importing ill health), and the impact on rural household livelihoods of migrants returning in ill health. The final section discusses the key conclusions and implications of the study. Using a large dataset collected in four counties in 2007, several key questions about return migrants are examined. Why did they return home? How did they seek or access medical services? Who was responsible for earning the household income and providing daily care? Did these migrants receive assistance from formal social security schemes? And what were the impacts on their household livelihoods?
Keywords: 330